The Effect of Application of PSAK 69: Agriculture on Assets Biological against the Company Value of Agro-Industry in Indonesia Stock Exchange - Yussi Stiefania (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
The treatment of biological assets has undergone a transformation which was previously measured using a cost-based approach, until January 1, 2018, the new rules of PSAK 69: Agriculture were effectively enforced, which implies fair value-based implementation. The existence of this new policy can affect several aspects of the company both in policy and in financial aspects, namely the resulting gain and loss on adjustments to biological assets. This will potentially affect the value of a company. This study reveals the facts related to whether there is an effect of the impact of the application of PSAK 69 on the value of the company that applies it. The quantitative approach is used and supported by secondary data collected through documentation techniques. The research sample was selected by purposive sampling method. The population of the research data was 21 agro-industrial companies listed on the IDX. Then as many as 15 companies (firm years) were declared to meet the sample criteria. This study is accompanied by two control variables: leverage and profitability. Data processing using statistical applications includes descriptive statistical test analysis techniques, classical assumption test, linear regression test, and hypothesis testing. The conclusions found by researchers are that there is a significant positive effect of the application of PSAK 69 on the value of agro-industrial firms, as well as the influence of leverage and profitability on firm value. Thus, the application of PSAK 69 can affect the increase or decrease in the value of agro-industrial companies.